The Why axis : hidden motives and the undiscovered economics of everyday life - Gneezy, Uri.; List, John A., 1968- (New York, NY : PublicAffairs, 2013)
A colorful examination of why people do what they do-- observed through the lens of incentives that can spur people to achieve-- as reviewed by two superstars revolutionizing economics.
Getting beyond assumptions : what makes people do what they do? -- How can you get people to do what you want? : when incentives (don't) work and why -- What can Craigslist, mazes, and a ball and bucket teach us about why women earn less than men? : on the plains below Kilimanjaro -- What can a matrilineal society teach us about women and competition? : a visit to the Khasi -- How can sad silver medalists and happy bronze medalists help us close the achievement gap? : public education : the $627 billion problem -- How can poor kids catch rich kids in just months? : a voyage to preschool -- What seven words can end discrimination? : I don't really hate you, I just like money -- Be careful what you choose, it may be used against you! : the hidden motives behind discrimination -- How can we save ourselves from ourselves? :using field experiments to inform life and death situations -- What really makes people give to charity? : don't appeal to people's hearts, appeal to their vanity -- What can cleft palates and opt-out boxes teach us about people's reasons for giving to charity? : the remarkable phenomenon of reciprocity -- Why is today's business manager an endangered species? : creating a culture of experimentation at your business -- How to change the world -- or at least get a better deal : life is a laboratory.
Includes bibliographical references (pages 247-256) and index.
Keywords: Economics -- Psychological aspects; Motivation (Psychology) -- Economic aspects